EFFICIENCY OF SODIUM SELENATE UTILIZATION IN TOMATOES PRODUCTION IN STRESS CONDITIONS - Z. A. Amagova; N. A. Golubkina (Овощи России, 2018)
Increase of plants resistance to adverse environmental factors is considered to be the basic factor affecting the production of sustainable yields and high quality of agricultural crops. Anomalously high and low temperatures, water logging and drought, bacterial infections and herbivore attack compose significant risk factors during cultivation of different agricultural crops including tomatoes. In last decades great attention is paid to the possibility of plants protection against oxidative stress via biofortification with selenium. Effect of selenium biofortification in adverse ecological conditions of the Chechen republic (high humidity and low temperature) on yield and biochemical characteristics of two tomatoes varieties (Utro, Krasny Velican) was investigated. Dose of 4 mg Se/sq. m in triple processing during vegetation resulted in 18.9-89.9% increase of fruit yield depending on the cultivar tolerance to cladosporium. For the first time the possibility of selenium utilization in protection of plants against cladosporium was demonstrated. Biofortification of plants with selenium resulted in 1,36-1.41 increase of ascorbic acid content, 1.1 times – of carbohydrates, 1.13- 1.22 times – of titratable acidity, 1.9-1.23 time – of betacarotene, 1.55-1.36 times – of licopene. Taste index of tomato fruit also increased by 10%. 16 Fold fortification level of tomato fruit provides 22-29 % from the adequate selenium consumption level with 300 g of the product.